Implementasi Project Based Learning untuk Meningkatkan Hasil Belajar Siswa Kelas III B Mata Pelajaran IPAS di MI Tarbiyatut Tholabah - Nur Lailah Fithri; Suheri Widianto (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
Learning natural and sosial sciences (IPAS) in elementary schools often faces challenges in improving students’ understanding, which is seen from the low learning outcomes. This study aims to evaluate the effectiveness of the implementation of the Project Based Learning (PjBL) Learning model in improving the understanding of natural and sosial sciense conceps (IPAS) in elementary school student. Elementary school IPAS learning often faces challenges in improving students’ understanding, which is reflected in the low learning outcomes. The method used is classroom action research (PTK) which was carried out in two cycles, involving 16 grade III Students at MI Tarbiyatut Tholabah Kranji Paciran. Data were collected through observation, test, and documentation, and analyzed qualitatively and quantitatively. The result showed that the implementation of the PjBL model significantly improved students’ understanding of IPAS concepts, with an increase in learning outcomes from cycle 1 to cycle 2. Observations also showed that students became more active and enthusiastic in participating in learning. Steps such as providing motivation, viding heterogeneous study groups, and opportunities for presentations contributed to positive results. This finding indicates that the PjBL learning model can be an affective alternative to improve the understanding of science concepts among elementary school students. This research is expected to contribute to the development of better curriculum and learning methods.